2017
DOI: 10.1007/s11695-017-2971-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Gastroesophageal Reflux Disease After Laparoscopic Sleeve Gastrectomy

Abstract: Symptoms of heartburn and regurgitation are common after LSG; however, none of the variables preoperatively could strongly predict patients who would develop new onset or experience worsening of symptoms postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 13 publications
4
40
0
2
Order By: Relevance
“…Our work which is currently under review showed 88% of reported GERD symptoms happened only post-prandial which suggest that the reflux symptoms after LSG may be related to nonacid volume reflux instead of acid reflux. This is consistent with Althuwaini et al which concluded 35.7% of regurgitation was nonacid food regurgitation [ 25 ]. Also there might be some unmeasured confounders, for example, smoking and alcohol consumption with GERD-Q or GERD-HRQL.…”
Section: Discussionsupporting
confidence: 92%
“…Our work which is currently under review showed 88% of reported GERD symptoms happened only post-prandial which suggest that the reflux symptoms after LSG may be related to nonacid volume reflux instead of acid reflux. This is consistent with Althuwaini et al which concluded 35.7% of regurgitation was nonacid food regurgitation [ 25 ]. Also there might be some unmeasured confounders, for example, smoking and alcohol consumption with GERD-Q or GERD-HRQL.…”
Section: Discussionsupporting
confidence: 92%
“…Dysgeusia also can be a persistent taste that is actually tasted, such as that caused by reflux. Gastroesophageal reflux, a side effect of morbid obesity as well as bariatric surgery [73], especially the sleeve gastrectomy [74], could contribute to a perception that things didn’t taste right or dysgeusia. The present study also was consistent with a previous report [45] that showed that post-bariatric surgery patients, especially if successful in weight loss, reported that they were better able to detect basic taste qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates reported by Althuwaini et al [23] , Boza et al [31] were 47.0% and 26.7% respectively. The possible explanation for this wide variance in prevalence could be attributed to different definitions of GERD; diagnostic methods used for confirmation of post LSG GERD and different inclusion criteria.…”
Section: Disucssionmentioning
confidence: 80%
“…This incidence lies with reported incidence in previous literature. Althuwaini et al [23] reported that although the majority of the patients did not develop new-onset symptoms or even had improved symptoms of GERD after LSG, there remained a significant proportion that developed new-onset symptoms or had worsening of symptoms of GERD after SG [ranging from as high as 35.7% for symptoms of regurgitation to as low as 16.0% for heartburn causing sleep disruption]. They concluded that some regurgitation was non-acid food regurgitation and hypothesized that regurgitation of gastric contents could have a major role in patient symptoms and might not be assessed completely by the questionnaire.…”
Section: Disucssionmentioning
confidence: 99%